Hubungan Antara Beban Kerja Dengan Kepatuhan Perawat Dalam Pendokumentasian Early Warning System (EWS) Di Ruang Rawat Inap Rumah Sakit Panti Rahayu Gunung Kidul - Widegdo, Hernyu; Marti, Eva; Ratnawati, Emmelia (STIKes Panti Rapih, 2022)
ABSTRACT Backgraund: The High workload causes nurses to not comply with documentation, causing small parts of the documentation to be missed. Especially at night where the number of nurses at night is small while the patients who are treated are many. Objective: The purpose of this study was to determine the relationship between the workload of nurses and compliance with EWS documentation in the inpatient setting at Panti Rahayu Hospital. Methods: This research design using quantitative with analytic observational survey with cross sectional approach. The population in this study amounted to 41 nurses. And taken a sample of 38 respondents who filled out the questionnaire, with a sampling technique in the form of total sampling with data collection techniques with a google form questionnaire. Result: From the unvariate results, it was found that respondents who work at Panti Rahayu Hospital Almost half are in the age range, 44.7% of late teens, almost all of them are female as much as 84.2%, Almost all of them have a D3 Nursing education background as much as 86.8% , Almost half of nurses with PKWT functional positions are 55.3%. From the bivariate results, almost half of the nurses have a moderate workload of 42.10% and most have a sufficient level of compliance as much as 65.8%, using the spearmant rank test, the correlation coefficient is -510 with a p-value of 0.001 (< 0.05), which means the higher the workload, the lower the compliance. Conlusion: There is a relationship between workload variables and compliance in EWS documentation. It is hoped that for nursing the results of this study can reduce the workload felt by nurses and can increase nurse compliance in carrying out EWS documentation at Panti Rahayu Hospital. Keyword : Workload, Compliance, EWS Documentation